Improving UV Protection of Cotton Fabrics Dyed with Peristrophe bivalvis Extract using UV Absorber - Rachma Tia Evitasari; Edia Rahayuningsih (CHEMICA: Jurnal Teknik Kimia, 2020)
UV radiation from the sun that constantly exposes the skin can cause skin damage such as sunburn and skin cancer. The damage from UV can be reduced by clothing. Increasing UV protection on cotton fabric can be done by adding UV absorbers. The effect of type, treatment, and concentration of UV absorber on cotton dyed with phenoxazine natural dyes from Peristrophe bivalvis was studied. Two types of UV absorber were used, benzophenone and benzotriazole. Concentrations of UV absorber used in this study ranging from 5% to 15% on weight of fabric applied on three treatments, before dyeing, after dyeing, and both. UV protection on the cotton fabric was expressed by the UV Protection Factor (UPF) value. Lightfastness, washing fastness and rubbing fastness were also performed using grayscale. The use of UV absorbers increases the UPF value of dyed cotton by before and after dyeing treatment. The best UPF value was achieved by adding benzotriazole with a concentration of 15% by before and after treatment resulting in a UPF value of 5.45. The results of light fastness, washing fastness, and rubbing fastness ware also improved by the addition of UV absorber.